Sustainability consciousness in higher education: Construction of three-dimensional sustainability and role of locus of control - Nina Farliana; Hanif Hardianto; Rusdarti Rusdarti; Wijang Sakitri (Sustinere: Journal of Environment and Sustainability, 2024)
This study aims to analyze the level of sustainability awareness among university students, especially focusing on their knowledge, attitudes, and behavior related to sustainability across three main dimensions: environmental, social, and economic. Additionally, the study explores whether these behaviors are influenced by individuals’ beliefs about their ability to effect change. This study employed a quantitative approach involving all active students enrolled in the Faculty of Economics and Business, Universitas Negeri Semarang. A samples of 233 respondents was selected using a non-probability sampling method. Data was collected through a questionnaire and analyzed using the Structural Equation Modeling Partial Least Square method. The study findings reveal that attitude towards sustainability have stronger influence on behavior than knowledge. Respondents' demonstrated a higher level of understanding of sustainability compared to their attitudes and behaviors towards it. Furthermore, concerns to economic aspects were found to impact sustainability behaviors. Most respondents expressed a belief that events around them are beyond their control. This article is expected to significantly contribute to aligning policies and practices, particularly in fostering sustainability awareness, and serve as a basis for achieving sustainable development initiatives.